2022
DOI: 10.1155/2022/8251220
|View full text |Cite
|
Sign up to set email alerts
|

How to Maintain a Sustainable Doctor-Patient Relationship in Healthcare in China: A Structural Equation Modeling Approach

Abstract: It is important to identify means of improving and maintaining a sustainable doctor-patient relationship to address current healthcare issues. Although many studies have made outstanding contributions to the healthcare doctor-patient relationship literature, little work has been done to explore the influencing elements of the doctor-patient relationship in relation to expectation confirmation theory. To fill this gap, this study produced a theoretical framework model of the influencing factors of the doctor-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…On a similar note, Kaczorowska et al 80 recognised product value as an essential indicator of consumers’ brand expectations and their decision of using the product. In a more recent study, Wang et al 82 demonstrated the significant influence of perceived value on consumers’ purchase intention. Based on the review of these findings, the following hypothesis was tested in this study:…”
Section: Literature Reviewmentioning
confidence: 99%
“…On a similar note, Kaczorowska et al 80 recognised product value as an essential indicator of consumers’ brand expectations and their decision of using the product. In a more recent study, Wang et al 82 demonstrated the significant influence of perceived value on consumers’ purchase intention. Based on the review of these findings, the following hypothesis was tested in this study:…”
Section: Literature Reviewmentioning
confidence: 99%